Active Cable Sheath Current-Based Protection Scheme for an Offshore HVAC Wind Transmission System - Zhao, Yang; Liu, Qing; Xia, Rong; Shang, Yingqiang (Frontiers in Energy Research, 2022)
Due to the complex sending terminal structure of offshore wind transmission system, conventional on-line monitoring-based protection cannot work well. The electromagnetic transient faults are also difficult to locate due to a short time span with fast characteristics that are affected by various power electronic devices and control algorithms. To solve the above problems, a new offshore wind transmission line protection scheme based on active detection of submarine cable sheath current is proposed. This method uses a normalized coding cooperation to realize the risk levels and failure locations of the transient defects, then the sheath currents become a characteristic input data source, which can build a clear system protection boundary. Cases studies by using MATLAB and ATP simulations are carried, with three types of transient faults represented by sheath currents are studied, i.e., loss of electrical continuity of grounding device, short circuit of segmented metal sheath of cable joint and water immersion of junction box. Testing results illustrated that the proposed method could achieve fast fault detection and precise fault location of the electromagnetic transients. Moreover, compared with conventional wind farm protection techniques, it only needs to add few signal injection modules with high sampling frequency into the submarine optical fibers.